2013
DOI: 10.1017/s0950268813000551
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of tuberculosis in patients with end-stage renal disease: a population-based cohort study in Taiwan, a country of high incidence of end-stage renal disease

Abstract: This nationwide population-based cohort study investigated the risk of tuberculosis (TB) in patients with end-stage renal disease (ESRD) and receiving dialysis. The evaluations included 4131 incident ESRD patients receiving dialysis and 16,524 age- and gender-matched controls, recruited between 1998 and 2009. We used Cox proportional hazards regression analysis to measure the association between TB and ESRD. Compared to the controls, the ESRD cohort had a significantly higher risk of TB within 1 year [incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
(29 reference statements)
1
17
0
6
Order By: Relevance
“…It is not known why only 10% of individuals infected with Mtb develop active disease. Apart from diverse risk factors such as diabetes, smoking, and chronic renal failure (Hu et al 2014), several genes have been found to be associated with increased susceptibility to, or resistance against, Mtb (Möller et al 2010).…”
Section: Clinical Presentation and Diagnosis Of Tb Pulmonary Tbmentioning
confidence: 99%
“…It is not known why only 10% of individuals infected with Mtb develop active disease. Apart from diverse risk factors such as diabetes, smoking, and chronic renal failure (Hu et al 2014), several genes have been found to be associated with increased susceptibility to, or resistance against, Mtb (Möller et al 2010).…”
Section: Clinical Presentation and Diagnosis Of Tb Pulmonary Tbmentioning
confidence: 99%
“…Patients with end stage renal disease receiving hemodialysis (ESRD) are also at an increased risk of TB, especially within 2 years of onset of ESRD (95). It has been estimated that incidence of TB in patients with ESRD is more than 10 times greater than in the general population (49).…”
Section: Medical Conditions Other Than Hivmentioning
confidence: 99%
“…1 The main reasons are impaired cell-mediated immunity, immunosuppressive medications, human immunodeficiency virus (HIV) co-infection, and diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%